Contrasting pectin polymers in guard cell walls of Arabidopsis and the hornwort Phaeoceros reflect physiological differences. (8th September 2018) - Merced, Amelia; Renzaglia, Karen S
Abstract: Background and Aims: In seed plants, stomata regulate CO2 acquisition and water relations via transpiration, while minimizing water loss. Walls of guard cells are strong yet flexible because they open and close the pore by changing shape over the substomatal cavity. Pectins are necessary for wall flexibility and proper stomata functioning. This study investigates the differences in pectin composition in guard cells of two taxa that represent key lineages of plants with stomata: Arabidopsis, an angiosperm with diurnal stomatal activity, and Phaeoceros, a bryophyte that lacks active stomatal movement. Methods: Using immunolocalization techniques in transmission electron microscopy, this study describes and compares the localization of pectin molecule epitopes essential to stomata function in guard cell walls of Arabidopsis and Phaeoceros . Key Results: In Arabidopsis, unesterified homogalacturonans very strongly localize throughout guard cell walls and are interspersed with arabinan pectins, while methyl-esterified homogalacturonans are restricted to the exterior of the wall, the ledges and the junction with adjacent epidermal cells. In contrast, arabinans are absent in Phaeoceros, and both unesterified and methyl-esterified homogalacturonans localize throughout guard cell walls. Conclusions: Arabinans and unesterified homogalacturonans are required for wall flexibility, which is consistent with active regulation of pore opening in Arabidopsis stomata. In contrast, the lack of arabinans and high levels of methyl-esterified homogalacturonans in guard cell walls of Phaeoceros are congruent with the inability of hornwort stomata to open and close with environmental change. Comparisons across groups demonstrate that variations in guard cell wall composition reflect different physiological activity of stomata in land plants.